Underserved women of color, voice, and resistance : claiming a seat at the table - Givens, Sonja M. Brown; Tassie, Keisha Edwards, 1976- (Lexington Books, 2014)
This book argues that contemporary research on the lives and experiences of women of color tends to neglect the influence of women's perceived access to voice on how they manage tensions related to race, class, and gender. This book explores the politics of pursuing voice by women of color across various social contexts.